The ends of the earth : an anthology of the finest writing on the Arctic and the Antarctic - Kolbert, Elizabeth; Spufford, Francis 1964- (Bloomsbury, 2007)
A literary anthology explores the natural wonders of the frozen landscapes of the Arctic and Antarctic in a compilation of first-person narratives, cultural histories, science and nature writing, and fiction.